Eco-Social Services of Native Tree Species: A Conservation Approach - Sahu, Lalit Mohan; Das, Kadambini; Sahu, Jaydeep Kumar; Das, Anuradha; Behera, Banshidhar; Kumar, Sanjeet (Indian Forester, 2024)
Trees are important aspects of life on earth. The preservation and restoration of forests have always been crucial for finding answers to the climate crisis. Still, a tenth or more of the world’s annual CO2 emissions is the result of 2 deforestation. Additionally, trees do much more than just storage of carbon. Additionally, they improve biodiversity, stabilise soil and other climatic conditions, cleaning, and recycling water. Deforestation by cutting down trees is advancing everywhere. In the name of development, the oldest trees are being cut down and replaced with invasive species in so many places. Awareness against the old and native tree species and their restoration should be done very quickly. Keeping this in mind, an attempt has been made to document the indigenous tree species of Odisha, India, along with their food, medicinal, economic, and mythological aspects. A survey was carried out from the year 2010 to 2023 in Odisha state under several projects and biodiversity works. Through field visits, interaction with locals, and direct observation, the information was collected. The survey revealed that trees are the lifeline of the ecosystems and are directly attached to the day-to-day work, culture, and emotions of people. These also have ecological, mythological, and cultural significance. These provide numerous services to human beings, which are documented in the paper. The present study highlights the importance of native trees and suggests planting more and more local tree species.